2017
DOI: 10.1089/neu.2016.4475
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Care Practices and Utilization of Evidence-Based Guidelines in the Evaluation and Management of Concussion: A Survey of New England Emergency Departments

Abstract: Evidence-based clinical practice guidelines can facilitate proper evaluation and management of concussions in the emergency department (ED), often the initial and primary point of contact for concussion care. There is no universally adopted set of guidelines for concussion management, and extant evidence suggests that there may be variability in concussion care practices and limited application of clinical practice guidelines in the ED. This study surveyed EDs throughout New England to examine current practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…According to the health care accreditation assessments, Jordan's hospital management system is oriented towards enabling hospitals to flourish in their organisational capacity (A'aqoulah, Kuyini, Ajlouni, Saif, & Al-Raoush, 2016). Conversely, it is also responsible for ensuring health care safety, based on primary facilities of organisational services (Stern et al, 2017). Accreditation has been defined as:…”
mentioning
confidence: 99%
“…According to the health care accreditation assessments, Jordan's hospital management system is oriented towards enabling hospitals to flourish in their organisational capacity (A'aqoulah, Kuyini, Ajlouni, Saif, & Al-Raoush, 2016). Conversely, it is also responsible for ensuring health care safety, based on primary facilities of organisational services (Stern et al, 2017). Accreditation has been defined as:…”
mentioning
confidence: 99%
“…To do this well, healthcare providers need knowledge, decision-support tools, and other resources to support the care of their patients (2). Yet, recent studies indicate that healthcare providers may not use available practise guidelines and resources (3,4). A 2013 survey of emergency department physicians found that 35% of physicians did not use evidence-based clinical practise guidelines to manage mTBI (3).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, recent studies indicate that healthcare providers may not use available practise guidelines and resources (3,4). A 2013 survey of emergency department physicians found that 35% of physicians did not use evidence-based clinical practise guidelines to manage mTBI (3). Another survey of paediatricians in Illinois found that only 14.6% used mTBI guidelines in their practise (4).…”
Section: Introductionmentioning
confidence: 99%
“…A recent regional study of pediatric providers reported that over half did not use guidelines in managing pediatric concussion patients (Itriyeva et al, 2016). Another recently published regional survey of New England emergency departments indicated that the majority reported having no concussion clinical practice guidelines (35%) or inconsistency in the type of concussion guidelines used (57%; Stern et al, 2016).…”
Section: Introductionmentioning
confidence: 99%